Combination of ATRA and ATRC for the Synthesis of Periodic Vinyl Copolymers. Issue 4 (4th December 2013) - Wang, Chun‐Hao; Song, Zi‐Yuan; Deng, Xin‐Xing; Zhang, Li‐Jing; Du, Fu‐Sheng; Li, Zi‐Chen; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> A new approach to periodic vinyl copolymers via combination of atom transfer radical addition (ATRA) and atom transfer radical coupling (ATRC) is reported. The two examples are methyl methacrylate (MMA) and styrene (St) periodic copolymer (P(SMMS)) and acrylonitrile (AN) and St periodic copolymer (P(SAAS)). First, two monomer sequence units (MSU) with built‐in sequence, SMMS and SAAS, are synthesized through the controlled ATRA of two ATRP initiators with St. Then, the ATRC of SMMS and SAAS are conducted at high radical conditions to generate two types of high‐molecular‐weight copolymers, P(SMMS) and P(SAAS). Though side reactions can not be totally avoided, characterizations of the polymer structure with a variety of means confirm that the main chain structures of P(SMMS) and (PSAAS) are predominantly with the periodic sequences from the MSUs. Attempts to suppress the side reactions are successful via the MNP‐mediated ATRC of SMMS and SAAS. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>